1994
DOI: 10.3758/bf03211676
|View full text |Cite
|
Sign up to set email alerts
|

Interpolation across surface discontinuities in structure from motion Asad Satdpour

Abstract: Interpolation across orientation discontinuities in simulated three-dimensional (3-D) surfaces was studied in three experiments with the use of structure-from-motion (SFM) displays. The displays depicted dots on two slanted planes with a region devoid of dots (a gap) between them. If extended through the gap at constant slope, the planes would meet at a dihedral edge. Subjects were required to place an SFM probe dot, located within the gap, on the perceived surface. Probe dot placements indicated that subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…These observations suggest that surface interpolation in three dimensions may proceed without contour interpolation. This 3-D surface spreading may be similar to effects observed in structure-from-motion displays (Saidpour, Braunstein, & Hoffman, 1994).…”
Section: Methodssupporting
confidence: 73%
“…These observations suggest that surface interpolation in three dimensions may proceed without contour interpolation. This 3-D surface spreading may be similar to effects observed in structure-from-motion displays (Saidpour, Braunstein, & Hoffman, 1994).…”
Section: Methodssupporting
confidence: 73%
“…The exact form of smooth, interpolated contours has proven difficult to determine, because many models make very similar predictions in many circumstances. Earlier work has looked at the shape of surface interpolation in structure-from-motion displays (Saidpour, Braunstein, & Hoffman, 1994). Saidpour et al found that the shapes of interpolated surfaces were smooth and dependent on the geometry of the motion-defined surface, consistent with 3-D extensions of the models proposed by Ullman (1976) and Kellman and Shipley (1991) or a 3-D model of shape interpolation based on minimization of the quadratic variation functional (Grimson, 1981).…”
Section: Theory Of 3-d Relatabilitymentioning
confidence: 99%
“…Two contours are relatable if they can be connected by a smooth curve that bends monotonically through no more than about 90°. A number of empirical studies of the contour interpolation process have suggested that the geometric notion of relatability describes the conditions under which observers perceive fragmented regions of objects as unified into a single perceptual unit for both occluded and illusory objects (e.g., Field et al, 1993; Kellman, Garrigan, Shipley, et al, 2005; Kellman & Shipley, 1991; Kellman et al, 1998; Saidpour, Braunstein, & Hoffman, 1994).…”
Section: Visual Unit Formation In Static Scenesmentioning
confidence: 99%